ANALISIS PERSEPSI SISWA MADRASAH ALIYAH TERHADAP PEMBELAJARAN MATEMATIKA BERBANTUAN TEKNOLOGI PADA PJJ SELAMA PANDEMI COVID-19 - Sulistiawati Sulistiawati (IKIP Siliwangi, 2023)
This research is based on the important role of technology as one of the supporters of learning during the Covid-19 pandemic. The purpose of this study was to investigate the perceptions of madrasah students regarding technology-assisted mathematics learning, differences in perceptions between male and female students, students' perceptions when viewed from the indicators, and students' opinions on distance learning during pandemic. This study uses descriptive methods with quantitative and qualitative approaches to students of MAN 2 Kota Sukabumi class Xmathsci. on the academic year 2020/2021. The instruments used are closed questionnaires and written interview questions that has been validated. The data analysis technique used an interval approach determined by the Ideal Mean (Mi) and the Ideal Standard Deviation (SDi) to determine the category of perception as well as verbal analysis. The conclusion obtained is that students have positive perceptions regarding technology-assisted learning in distance learning, both male and female students have positive perceptions, and students' opinions about the distance learning that has been implemented are mostly the learning experiences are to use Google Classroom and then WhatsApp.